2022
DOI: 10.3390/nu15010100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Supplement Use in Sport Climbers at Different Climbing Levels

Abstract: The lack of specific recommendations on the use of supplements for sport climbers may be the reason for their misuse by athletes of this discipline. This study aimed to evaluate choices of dietary supplementation, the reasons for taking them, and the source of information on supplementation among sport climbers at different levels. In addition, how climbers subjectively evaluated the impact of their diets in supporting selected aspects of climbing training was evaluated. We enrolled 110 regular sport climbers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…An assessment of nutritional knowledge or strategies of weight loss has not been previously reported in climbing athletes. Furthermore, only one previous study has assessed prevalence or sources of influence of supplement use in recreational climbers ( 33 ), and none have examined competition climbers specifically. Therefore, the aim of this study was to firstly, assess the current nutrition knowledge of competition climbers and identify gaps which may inform education programs to support health and performance; secondly, develop a greater understanding of the magnitude, sources of influence, and strategies of weight loss in competition climbers; and lastly, to identify the prevalence, rationale, and sources of influence of supplement use in competition athletes.…”
Section: Introductionmentioning
confidence: 99%
“…An assessment of nutritional knowledge or strategies of weight loss has not been previously reported in climbing athletes. Furthermore, only one previous study has assessed prevalence or sources of influence of supplement use in recreational climbers ( 33 ), and none have examined competition climbers specifically. Therefore, the aim of this study was to firstly, assess the current nutrition knowledge of competition climbers and identify gaps which may inform education programs to support health and performance; secondly, develop a greater understanding of the magnitude, sources of influence, and strategies of weight loss in competition climbers; and lastly, to identify the prevalence, rationale, and sources of influence of supplement use in competition athletes.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to meet the recommended 15 mcg of vitamin D intake from the diet, and vitamin D supplementation is recommended for the Polish population during all seasons because of insufficient sun exposure [ 38 ]. However, no more than 33% of climbers declared using vitamin D supplements [ 20 ]. Nonetheless, the available data show that, although the correction of vitamin D deficiency is necessary, additional supplementation may not have added health benefits [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, research has found inadequate energy availability (EA) [ 7 ], unbalanced food quality, and poor nutrient timing in the diets of climbers of different ages and levels of advancement [ 18 ]. Furthermore, several studies have investigated supplement use in sports climbers [ 12 , 19 , 20 ] and analyzed supplement protocol use [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Potential side effects of excessive supplement use consist of kidney injury, gastrointestinal discomfort, hypercalcemia, and an increased risk of cardiovascular diseases (39). Furthermore, a signi cant percentage of European and American dietary supplements, from 10-25%, may pose a potential risk of doping (40), while more recent data suggest an even higher rate of 38% (41). Given this grave situation, our questionnaire aims to shed light on the appropriate consumption of sports supplements to enhance the knowledge and understanding of athletes in this area.…”
Section: Discussionmentioning
confidence: 99%